Answer:
5,814
Step-by-step explanation:
19 × 18 × 17
5,814
Answer:
No.
Step-by-step explanation:
f(x) = 3x^4-4x^2-3
If a function is odd then f(-x) = -f(x) for all values of x.
Here f(-x) = 3(-x)^4 - 4(-x)^2 - 3
= 3x^4 - 4x^2 - 3
So f(-x) = f(x) which makes it even.
<span>Just graph the function up to and/or including the points indicated.
- if you have a piecewise function defined as y=x when x < 0
y=-x when x >=1
You would graph y=x from the negative direction up to 0 (but leaving an open circle on 0 because the function is not defined there
Then start at point 1 (this time with a closed circle because y=-x is defined at 1, and graph y=-x.</span>